Measuring the Effectiveness of State Civil Apparatus Training - Rahayu, Neneng; Suryanto, Adi; Andriansyah, Andriansyah; Irawati , Erna (LifeSciFi, 2022)
The study discusses the crucial role of training evaluation for State Civil Apparatus (Aparatur Sipil Negara or ASN) and how the shift to distance learning methods, particularly during the COVID-19 pandemic, has impacted training effectiveness. The evaluation aims to measure the impact of training on participants’ knowledge, skills, and attitudes, as well as its effects on the organizations. The results of the evaluation indicate that distance learning is preferred by alumni due to its flexibility, but there is a need for higher-quality facilitators in delivering content via information technology. Despite the remote nature of training, participants still achieve their intended competencies. The evaluation also assesses the impact of training on participants’ behavior and workplace performance. Notably, National Leadership Training Level I and II have a more positive influence on sustainability and work performance when using blended learning, while Administrator Leadership Training, Supervisory Leadership Training, and the Pre-Service Training Program show a stronger impact on sustainability and work performance with distance learning. The findings emphasize the significance of the chosen learning method in shaping training outcomes. This information is valuable for refining training policies to meet the evolving demands of the bureaucracy.